An Account of ‘Life after Guantánamo’: a rehabilitation project for former Guantánamo detainees across continents - Polly Rossdale; Katie Taylor (Torture)
This paper describes a project established in 2009 by the human rights charity, Reprieve, to coordinate rehabilitation for men who have been released from long-term detention at the US military base of Guantánamo Bay.  The majority of the men referred to the project were deemed unable to return to their home country because of the risk they faced of torture or other persecution and were therefore resettled in a third country. This paper also refers to Tunisian former Guantánamo detainees with whom Reprieve worked, who had initially been resettled in a third country but then following the Jasmine Revolution and the fall of the Ben Ali regime, were able to return to their home country.  Reprieve then provided assistance to them and their families under the Life after Guantánamo in Tunisia project.  This paper briefly outlines the abuse and nature of psychological control at Guantánamo and, based on the first-hand experiences of the Project Coordinator and Caseworker, offers non-clinical observations of the apparent consequences of this control on the former detainees who were referred to the project. The Life after Guantánamo project facilitated social, medical, psychological, legal and financial assistance in partnership with local service providers and through liaison with host governments and intergovernmental organisations, such as the International Organisation for Migration (IOM), United Nations High Commissioner for Refugees (UNHCR) and the International Committee of the Red Cross (ICRC).  The paper recounts the type of assistance provided, highlights some of the challenges faced and, based on learnings made over the project’s eight year duration, makes recommendations, for future work with former Guantánamo detainees and others who have been detained and subject to torture and inhuman and degrading treatment in the ‘War on Terror’.